Evaluasi pengaruh pengungkapan elemen integrated reporting terhadap asimetri informasi - Yolanda, Indah Septi; Fauziya, Ahada Nur (Master Program in Accounting, Faculty of Economics, Universitas Islam Indonesia, 2024)
The purposes of this study aims to empirically prove that the elements that contained in integrated reporting have an influence on information asymmetry. The population being used in this study are companies that run their businesses in mining sector that are listed on the Indonesia stock exchange for period 2017-2021. This study uses quantitive data. Numbers of companies included in this study were 25 with research period of 5 years. The sampling technique used on this study were purposive sampling using certain criteria and obtain 125 samples. Data analysis techniques used in this study is multiple linear regression. Result on this study shows that disclosure of integrated reporting elements such as organizational environment, corporate governance, business models, risks and opportunities, strategy and resource allocation, performance, outlook, and basic of presentation do not significantly influence information asymmetry.